Case Study on Communication Behavior of Women SHGs Promoted By Lupin Human Welfare and Research Foundation - Kumari Manisha; K. N. Krishnakumar (Indian Journal of Extension Education, 2013)
Jyoti Bai a resident of Rajalwadi rural area earlier was involved in agriculture in her small piece of farm to earn two square meals for the family. Her husband used to work as daily wage driver. He usually got work for only few days in a month. For remaining days of months, he remained idle. Family’s monthly income was merely `1000-1500. This income did not suffice for even two square meals for the family, so educating children was beyond their imagination. One day Jyoti came to the Lupin HWRF office and explained her predicament. Lupin suggested her to form a self help group, through which she could do some activity. After the formation of Shivam SHG and once she become a member of SHG organization, she was provided with a loan of ` 0.06 lakhs at first, consequently she took second loan of ` 0.12lakhs, then third loan of ` 0.40lakhs and then ` 0.66lakhs, which she used to start up a Kirana shop and for running a truck business by taking truck on rent for her husband. The financial support from the bank and the couple’s enterprising nature has enabled them to earn ` 6000-7000 per month. In the village six women’s SHGs have been formed through her help. Jyoti arranges meetings of the groups regularly and keeps account of all banking for these groups. She inspires other members of SHGs to get socially and economically empowered. Other women in her village aspire to start economic activities on the line of Jyoti so that they can not only help their family but also feel economically empowered to bring-up their children better.Her life mission now is to help poor women of the village. Jyoti’s hard labor and dedication has brought happiness to the family and her example is paving the way for many other families to come up in life through self effort.